Techno self online learning PEVAR as a new learning alternative: Paradigm and construction - Failasuf Fadli; Chatarina Asri Budiningsih; Sugeng Bayu Wahyono; Sukirno Sukirno; Karthikeyan Parthasarathy; Razana Juhaida Johari (International Journal of Evaluation and Research in Education (IJERE), 2022)
This article aims to build paradigms, strategies, and stages of learning models that can reduce learning barriers. The learning process can benefit changes in cognitive, affective, and psychomotor aspects for the better. This research was conducted because it saw the reality of the problem of low learning achievement. This was qualitative study employed induction approach. The analysis of generic analytic style employed as theory development. This research found an online independent learning model consisting of five stages: preparation, exploration, verification, analysis, and reflection called PEVAR. Techno self online learning PEVAR offers a technology-based self-study alternative. Techno self online learning PEVAR is built based on the paradigm of behaviorism, constructivism, and cognitive. This learning model increases learning achievement, which is marked by increasing students' affective, cognitive, and psychomotor abilities. The strategies used to achieve the goals are commitment, discipline, motivation, confidence, creativity, activity, effectiveness, and efficiency in learning.